Risk factors and progression of the left ventricular myocardial hypertrophy - Lazutkina A.Yu.; Gorbunov V.V. (Саратовский научно-медицинский журнал, 2015)
Tftea/mofthis workisto study the left ventricular myocardial hypertrophy. Materials and methods: In the study that was held in period from 2008 to 2013 years and covers group of 7959 workers of locomotive brigades of Transbaika-lian railway. In stated period each individual was additionally searched for the risk factors and lesions in target-organs in time of medical examinations undergoing. Results: During the study in group (7959 observations with the terminal outcomes) 597 cases of the left ventricular myocardial hypertrophy were found and statistically analyzed. It has been found that arterial hypertension, age, retinopathy, diabetes mellitus, thickening of the intima — media complex of more than 0.9 mm/atherosclerotic plaques of the carotid arteries, body mass index >25.0, and atherosclerosis of the aorta, hyperglycemia and stress led to the development of the left ventricular myocardial hypertrophy. Conclusions: This causative and effect conditionality should be considered in the prevention and treatment of the left ventricular myocardial hypertrophy.